A new method of haemodynamic assessment of mitral stenosis in atrial fibrillation: construction of a nomogram. Issue 6 (December 1990) - Davies, S W; Gardener, J E; Bowker, T J; Timmis, A D; Balcon, R
Abstract : Accurate haemodynamic assessment of mitral stenosis by hydraulic formulas requires measurement of the mean valve gradient and the cardiac output. The calculation is laborious, particularly in the presence of atrial fibrillation when averaged values obtained from multiple beat-to-beat determinations must be used. The relations between valve area, end diastolic gradient, and heart rate in 20 patients with mitral stenosis and atrial fibrillation were examined. In each patient the end diastolic pressure gradient for each cardiac cycle was related linearly to the RR interval of that cycle, and this relation was unchanged on exercise. The slope (S) and intercept (I) of this relation correlated with the degree of mitral stenosis as measured by the Gorlin valve area. The regression equations describing these relations were then used to construct a nomogram relating end diastolic pressure gradient to mitral valve area at different heart rates. When the nomogram was applied to catheterisation data from a further 30 patients the results correlated well with direct calculation of valve area by the Gorlin formula. The nomogram is simple to use, does not require measurement of cardiac output, and is independent of heart rate so that it is unnecessary for the patient to exercise during catheterisation.